WhatsApp Groups in Teaching and Learning - Affah Mohd Apandi (Development in Language Studies, 2022)
The coronavirus pandemic has generated changes in the teaching-learning process in higher education institutions. As a result, most universities have shifted to online, where teaching is undertaken remotely and on digital platforms. Much attention has been given to second language teaching and learning in higher education. Whether it is language apps, video conferencing tools, virtual tutoring or online learning software, there has been a significant surge in usage since COVID-19. However, learners still have limited opportunities to use the language online and they are not able to stay online for a longer time. Therefore, Mobile-assisted language learning (MALL) has opened up a gateway for educators and learners to enhance second language teaching and learning by taking it into the real world. This study aims to solve the lack of communicative learning opportunities by introducing WhatsApp groups with MALL. A field observation with 35 students from one English class at Universiti Tun Hussein Onn was conducted to investigate the perception of students towards the use of WhatsApp groups as a motivational tool to develop their English usage. The results suggest that WhatsApp group helps to create language engagement, which effectively motivates the learners further. WhatsApp groups can help to reinforce classroom topics and improve conversations, collaborative work, and even writing. Therefore, WhatsApp groups are promising in English learning for higher institution students.